2021
DOI: 10.3390/diagnostics11030566
|View full text |Cite
|
Sign up to set email alerts
|

Abilities of Pre-Treatment Inflammation Ratios as Classification or Prediction Models for Patients with Colorectal Cancer

Abstract: Background: Systemic inflammatory status is known as an important factor of colorectal cancer prognosis. Our study aimed to evaluate the performances of inflammation biomarker ratios as classification models of seven outcomes in patients with colorectal cancer. Methods: A retrospective cohort study was conducted on subjects with colorectal cancer over five years at a single center in Transylvania, Romania. Seven derived ratios were calculated based on laboratory data: neutrophil-to-lymphocyte (NLR), derived ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Lastly, pre-treatment PNI was significantly correlated with response to CRT ( 9 , 30 ). In other studies, PNI did not give information of prediction for chemo- or radiotherapy ( 31 ). These discrepancies imply that these indicators may be unstable for the prediction of the response for CRT.…”
Section: Discussionmentioning
confidence: 86%
“…Lastly, pre-treatment PNI was significantly correlated with response to CRT ( 9 , 30 ). In other studies, PNI did not give information of prediction for chemo- or radiotherapy ( 31 ). These discrepancies imply that these indicators may be unstable for the prediction of the response for CRT.…”
Section: Discussionmentioning
confidence: 86%
“…The univariate analysis showed that NLR was related to the postoperative and chemotherapy prognosis and can be used as a predictor of death. 54 NLR also correlated with age, sex, location, death, T stage, N and M stage of CRC. On the other hand, some authors indicate that evaluation NLR and other ratios derived from morphology, show limited performance and clinical utility upon the ROC analysis.…”
Section: Inflammation-related Biomarkersmentioning
confidence: 85%
“…The combination of both can be used as a marker reflecting the inflammatory response in the course of cancer. Data from Ciocan et al 54 …”
Section: Inflammation-related Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophil-to-lymphocyte ratio NLR neutrophils (count/µL) lymphocytes (count/µL) [34] 3. Derived neutrophil-to-lymphocyte ratio dNLR neutrophils (count/µL) [leucocytes (count/µL)−neutrophils (count/µL)] [34,35] 4.…”
Section: Nomentioning
confidence: 99%